Perception Of Politeness In Requests By Indonesian Learners Of English As A Foreign Language - Waluyanti, Eko, Agus Wijayanto, Ph.D, Siti Zurhriah Ariatmi, M. Hum (2014)
This study focuses on analyzing the perception of politeness in requests by EFL leraners. This study aim at 1) describes the perception of the learners for the politeness in requests in some different social situation produced by Indonesian EFL learners, 2) describe the different perception of politeness used in request between males and females , 3) classified the reasons provided by Indonesian EFL students to judge politeness used in requests. This research applies descriptive qualitative method in which the research participants were fourty Indonesian EFL learners in Muhammadiyah Universty of Surakarta. The data were the perception of politeness used in request which provided in three scale polite, impolite and I don't know. The way to collect data is using documentation and questionare form of DCT (Discourse Completion Task) scenarios. The subject of this research were taken through a random sampling technique consisting of 40 students comprising 20 males and 20 females participants who were in seventh semester. The writer analyzed the data by using politeness theory by Brown and Levinson (1987), impoliteness theory by Culpeper (2010), and the last request theoty by Trosborg (1995). The result show that there were perceptions to judge politeness used in requests which provided by Indonesian EFL learners, the students regarded that indirect request included polite and direct request was considered impolite. The difference perception also happened between males and females to make judgements. Female had better perception about politeness on request than male because in mostly DCT female have more confidence to judge whether the utterance of request polite or impolite. But, male prefer to not make judgements in politeness request. The writer found several reasons to judge politeness, there were fourteen kinds of reasons which provided by Indonesian EFL learners. It could be seen total of the reasons, Word choice as 35,86%, modal verb as 16,53%, habitual action as 7,78%, distance as 10,97%, strategy of request as 4,72%, type of sentence as 5,69%, emotion as 2,5%, right as 0,83%, intonation as 4,86%, exclamatory mark as 2,08%, expression of face as 0,14%, culture as 0,55%, attention getter as 0,14%, and condition as 0,42%. In fact, there were some students doesn't give reason because the participants not sure whether the request polite or impolite.